HUBUNGAN KOMUNIKASI EFEKTIF PETUGAS BPJS DENGAN TINGKAT KEPUASAN LAYANAN PESERTA BPJS DI DESA INDRASARI KABUPATEN BANJAR TAHUN 2026 - Sevia Yuli Yana; M. Noor Ifansyah; Diana Pefbrianti; Fahriadi (LPPM Universitas Awal Bros, 2026)
Effective communication is one of the key factors in improving service quality and participant satisfaction in BPJS Health services. Unclear information, lack of responsiveness from officers, and limited participant understanding of service procedures may affect service satisfaction. This study aimed to analyze the relationship between effective communication of BPJS officers and the level of service satisfaction among BPJS participants in Indrasari Village, Banjar Regency, in 2026. This research employed a quantitative method with a descriptive correlational design and a cross-sectional approach. The study population consisted of 8,635 active BPJS participants, with a sample of 100 respondents selected using stratified random sampling. Data were collected through questionnaires and analyzed using univariate analysis and Fisher’s Exact Test. The results showed that the majority of respondents perceived BPJS officers’ communication as effective (81%) and reported satisfaction with the services provided (81%). Bivariate analysis revealed a significant relationship between effective communication and participant service satisfaction (p-value = 0.001). These findings indicate that clear, responsive, and empathetic communication plays an important role in enhancing participant satisfaction with BPJS services. Therefore, improving officers’ communication competencies through regular training and service evaluations is essential to support service quality improvement and increase participant satisfaction.